Forsskamide, a new ceramide from aerial parts of Forsskaolea tenacissima Linn. Issue 20 (18th October 2018) - Assaf, Hamdy K.; Nafady, Alaa M.; Allam, Ahmed E.; Hamed, Ashraf N. E.; Kamel, Mohamed S.; Shimizu, Kuniyoshi
Abstract: Although the various folk medicine uses and the biological activity of Forsskaolea tenacissima L., few chemical constituents of this plant have been reported, this provoked us to make our study. Forsskamide, a new ceramide was isolated from aerial parts of F. tenacissima L. (Urticaceae). The chemical structure was established by different spectroscopic methods ( 1 H, 13 C-NMR, HMBC, HSQC, ROESY, FAB-MS and HR-FAB-MS). Forsskamide showed a moderate cytotoxic activity by (MTT) method against human colorectal carcinoma cell line (HCT-116) with IC50 33.25 μM in comparison with 5-fluorouracil IC50 26.42 μM. While, it did not show any activity against human hepatocarcinaoma cell line (HepG-2). Abstract :